Reversal of deficits in aged skeletal muscle during disuse and recovery in response to treatment with a secrotome product derived from partially differentiated human pluripotent stem cells - Dennis K. Fix; Ziad S. Mahmassani; Jonathan J. Petrocelli; Naomi M.M.P. de Hart; Patrick J. Ferrara; Jessie S. Painter; Gabriel Nistor; Thomas E. Lane; Hans S. Keirstead; Micah J. Drummond (GeroScience, 2021)
Aged individuals are at risk to experience slow and incomplete muscle recovery following periods of disuse atrophy. While several therapies have been employed to mitigate muscle mass loss during disuse and improve recovery, few have proven effective at both. Therefore, the purpose of this study was to examine the effectiveness of a uniquely developed secretome product (STEM) on aged skeletal muscle mass and function during disuse and recovery. Aged (22 months) male C57BL/6 were divided into PBS or STEM treatment ( n = 30). Mice within each treatment were assigned to either ambulatory control (CON; 14 days of normal cage ambulation), 14 days of hindlimb unloading (HU), or 14 days of hindlimb unloading followed by 7 days of recovery (recovery). Mice were given an intramuscular delivery into the hindlimb muscle of either PBS or STEM every other day for the duration of their respective treatment group. We found that STEM-treated mice compared to PBS had greater soleus muscle mass, fiber cross-sectional area (CSA), and grip strength during CON and recovery experimental conditions and less muscle atrophy and weakness during HU. Muscle CD68 +, CD11b + and CD163 + macrophages were more abundant in STEM-treated CON mice compared to PBS, while only CD68 + and CD11b + macrophages were more abundant during HU and recovery conditions with STEM treatment. Moreover, STEM-treated mice had lower collagen IV and higher Pax7 + cell content compared to PBS across all experimental conditions. As a follow-up to examine the cell autonomous role of STEM on muscle, C2C12 myotubes were given STEM or horse serum media to examine myotube fusion/size and effects on muscle transcriptional networks. STEM-treated C2C12 myotubes were larger and had a higher fusion index and were related to elevated expression of transcripts associated with extracellular matrix remodeling. Our results demonstrate that STEM is a unique cocktail that possesses potent immunomodulatory and cytoskeletal remodeling properties that may have translational potential to improve skeletal muscle across a variety of conditions that adversely effect aging muscle.

Gender differences in respiratory health outcomes among farming cohorts around the globe: findings from the AGRICOH consortium - Jonathan Fix; Isabella Annesi-Maesano; Isabelle Baldi; Mathilde Boulanger; Soo Cheng; Sandra Cortes; Jean- Charles Dalphin; Mohamed Aqiel Dalvie; Bruno Degano; Jeroen Douwes; Wijnand Eduard; Grethe Elholm; et al. (Journal of Agromedicine, 2021)